A nearshore Hirnantian brachiopod fauna from South China and its ecological significance. (March 2020) - Huang, Bing; Rong, Jiayu; Harper, David A.T.; Zhou, Hanghang
Abstract: The brachiopods collected from the Kuanyinchiao Beds (Hirnantian, uppermost Ordovician) in Meitan and Zunyi counties, northern Guizhou, include 13 species and one undetermined taxon, dominated by Hirnantia sagittifera (M'Coy, 1851 ) (which accounts for over one-third of the specimens), together with common Eostropheodonta hirnantensis (M'Coy, 1851 ). They are assigned to the Hirnantia – Eostropheodonta Community, which probably inhabited a shallow-water, nearshore Benthic Assemblage (BA) 2 to upper BA 3 environment. Population analysis shows that the community was well adapted to this environment after the first phase of the end-Ordovician mass extinction. Representative specimens of all the species are illustrated, and a new species, Minutomena missa, is described herein. The variation in Hirnantia sagittifera was noted in many of previous studies but was not statistically evidenced. Here we have measured representative specimens of that famous species from the major paleoplates and terranes in the world, along with other species assigned to the genus from South China. Having used principal component analysis (PCA), significant variations in the species are documented statistically and revised, and three nominal species, one subspecies, and two morphotypes are now reassigned to Hirnantia sagittifera sensu stricto. UUID: http://zoobank.org/references/3f83fb1e-a6dd-4585-9f9f-9586dad28244